Direct Seeded Rice: A New Technology for Enhanced Resource-Use Efficiency - Bista, Bishal (International Journal of Applied Sciences and Biotechnology, 2018)
Rice (Oryza sativaL.) is a major staple food crop that feeds around 60% of the world’s population. It is a major food crop in terms of production, economy and is grown in all ecological zones of Nepal. In Nepal, traditional method of rice cultivation is widely accepted in which 20-25 days old seedlings are transplanted in the puddled field. Looming water scarcity, water-intensive traditional method of rice cultivation, escalating labour costs pressurize the development of alternative which is highly sustainable and profitable. Direct-seeded rice (DSR) offers a very good opportunity that can cope up the global need and reduces the water use to 50%, labour cost to 60% and increases productivity by 5-10%. It involves sowing of pre-germinated seeds into wet soil surface (wet seeding), dry soil surface (dry seeding) and standing water (water seeding). Weeds are the major constraint in direct-seeded rice (DSR) reducing the crop yield upto 90% and sometimes even crop failure. Enhanced nutrient use efficiency and integrated weed management can produce comparable yields to that of transplanted rice (TPR) encouraging many farmers to switch to DSR. Methane gas emission is significantly lower in DSR than in conventionally tilled puddled transplanted rice mitigating the world’s threat of global warming. Blast disease and root-knot nematode (RKN) are other important problems associated with DSR. Based on the evidences collected, the article reviews integrated package of cultivation technologies associated with DSR, advantages, constraints and likeliness of DSR to be the future of rice cultivation in Nepal. Int. J. Appl. Sci. Biotechnol. Vol 6(3): 181-198